The effect of mussel bed structure on the associated infauna in South Africa and the interaction between mussel and epibiotic barnacles - Jordaan, Tembisa Nomathamsanqa (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
Mussels are important ecological engineers on intertidal rocks where they create habitat that contributes substantially to overall biodiversity. They provide secondary substratum for other free-living, infaunal or epifaunal organisms, and increase the surface area for settlement by densely packing together into complex multilayered beds. The introduction of the alien invasive mussel Mytilus galloprovincialis has extended the upper limit of mussels on the south coast of South Africa, potentially increasing habitat for associated fauna. The aim of this study was to describe the structure of mussel beds, the general biodiversity associated with multi- and monolayered mussel beds of indigenous Perna perna and alien M. galloprovincialis, and to determine the relationship between mussels and epibiotic barnacles. This was done to determine the community structure of associated macrofauna and the role of mussels as biological facilitators. Samples were collected in Plettenberg Bay, South Africa, where M. galloprovincialis dominates the high mussel zone and P. perna the low zone. Three 15 X 15 cm quadrats were scraped off the rock in the high and low zones, and in the mid zone where the two mussel species co-exist. The samples were collected on 3 occasions. In the laboratory mussel-size was measured and sediment trapped within the samples was separated through 75 Î¼m, 1 mm and 5 mm mesh. The macrofauna was sorted from the 1 mm and 5 mm sieves and identified to species level where possible. The epibiotic relationship between mussels and barnacles was assessed by measuring the prevalence and intensity of barnacle infestation and the condition index of infested mussels. Multivariate analysis was used on the mean abundance data of the species for each treatment (Hierarchical clustering, multidimensional scaling, analysis of similarity and similarity of percentages) and ANOVA was used for most of the statistical analyses. Overall, the results showed that tidal height influences the species composition and abundance of associated fauna. While mussel bed layering influenced the accumulation of sediments; it had no significant effect on the associated fauna. Time of collection also had a strong effect. While there was an overlap of species among samples from January, May and March, the principal species contributing to similarity among the March samples were not found in the other two months. The outcomes of this study showed that low shore mussel beds not only supported a higher abundance and diversity of species, but were also the most structurally complex. Although the condition index of mussels did not correlate to the percentage cover of barnacle epibionts, it was also evident that low shore mussels had the highest prevalence. The levels of barnacle infestation (intensity) for each mussel species were highest where it was common and lowest where it was least abundant. This is viewed as a natural artefact of the distribution patterns of P. perna and M. galloprovincialis across the shore. Mussels are more efficient as facilitators on the low mussel zone than the high mussel zone possibly because they provide habitats that are more effective in protecting the associated macrofauna from the effects of competition and predation, than they are at eliminating the effects of physical stress on the high shore. Although mussels create less stressful habitats and protect organisms from the physical stress of the high shore, there are clear limitations in their ability to provide ideal habitats. The biological associations in an ecosystem can be made weak or strong depending on the external abiotic factors and the adaptability of the affected organisms.
Keywords: Mytilidae -- South Africa; Mytilus galloprovincialis -- South Africa; Mussel culture -- South Africa; Shellfish culture -- South Africa; Perna -- South Africa; Barnacles -- South Africa; Mussels -- South Africa; Mussels -- Ecology; Barnacles -- Ecology